Multidelay Arterial Spin-Labeling MRI in Neonates and Infants: Cerebral Perfusion Changes during Brain Maturation - Kim, H.G.; Lee, J.H.; Choi, J.W.; Han, M.; Gho, S.-M.; Moon, Y. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Arterial spin-labeling with multiple postlabeling delays can correct transit times. We tried to evaluate CBF in neonates and infants using multidelay arterial spin-labeling.MATERIALS AND METHODS: Multidelay arterial spin-labeling was applied to 13 preterm neonates (mean postmenstrual age, 34.9 weeks), 13 term-equivalent-age neonates (mean postmenstrual age, 39.2 weeks), and 6 infants (mean postmenstrual age, 57.8 weeks). Transit time–corrected CBF in the caudate, thalamus, frontal GM, occipital GM, frontal WM, and occipital WM was measured, and relative CBF compared with the whole-brain CBF was calculated. Inter- and intragroup comparisons were performed among the 3 age groups. A correlation and nonlinear regression analysis were performed between postmenstrual age and CBF.RESULTS: Intergroup comparisons showed significantly higher whole-brain CBF in infants (38.3 mL/100 g/min) compared with preterm (15.5 mL/100 g/min) and term-equivalent-age (18.3 mL/100 g/min) neonates (P < .001). In the intragroup comparison, all 3 groups showed significantly higher relative CBF values in the occipital WM (63.6%–90.3%) compared with the frontal WM (46.3%–73.9%). In term-equivalent-age neonates, the occipital GM (120.8%) had significantly higher relative CBF values than the frontal GM (103.5%). There was a significant negative correlation between postmenstrual age and the relative CBF of the thalamus (r = − 0.449, P = .010). There were significant positive relationships between postmenstrual age and the relative CBF of the frontal WM (R2 = 0.298, P = .001) and occipital WM (R2 = 0.452, P < .001).CONCLUSIONS: Multidelay arterial spin-labeling with transit time–corrected CBF showed developmental changes and regional differences of CBF in neonates and infants.ASLarterial spin-labelingF-GMfrontal GMF-WMfrontal WMO-GMoccipital GMO-WMoccipital WMPLDpostlabeling delayPMApostmenstrual agerCBFrelative CBFT1blongitudinal relaxation time of bloodTEAterm-equivalent-agewbCBFwhole-brain CBF